Design concept of a four wheeled hydrostatic drive oil palm fruit bunch collection-transportation machine - Ali, M. E.; Yahya, Azmi (Universiti Putra Malaysia, 1999)
A new machine system concept has been described in this paper to improve the productivity for infield collection-transportation of fruit bunches in the oil palm plantation industry. This proposed four wheeled hydrostatic drive integrated machine system is capable of collecting-transporting the fruit bunches in the field and transporting-unloading the collected fruit bunches directly into the main line transporter at the roadside. The overall construction of the machine consists of the main chassis and driving unit, collection assembly, scissors lift type fruit bin, and associated hydraulic control unit. Various functional components within the machine were hydraulically operated through a solenoid control system. AutoCAD R14 software package was employed to develop the scaled 3D conceptual model of the proposed machine system. Computations were made for determining the machine's total power requirements in accordance to the local terrain conditions.